Characterization of the MexC-MexD-OprJ Multidrug Efflux System in ΔmexA-mexB-oprM Mutants of Pseudomonas aeruginosa - Gotoh, Naomasa (American Society for Microbiology, 1998)
Expression of the multidrug efflux system MexC-MexD-OprJ in nfxB mutants of Pseudomonas aeruginosa contributes to resistance to fluoroquinolones and the “fourth-generation” cephems (cefpirome and cefozopran), but not to most β-lactams, including the ordinary cephems (ceftazidime and cefoperazone). nfxB mutants also express a second multidrug efflux system, MexA-MexB-OprM, due to incomplete transcriptional repression of this operon by the mexR gene product. To characterize the contribution of the MexC-MexD-OprJ system to drug resistance in P. aeruginosa, a site-specific deletion method was employed to remove the mexA-mexB-oprM region from the chromosome of wild-type and nfxB strains of P. aeruginosa. Characterization of mutants lacking the mexA-mexB-oprM region clearly indicated that the MexC-MexD-OprJ efflux system is involved in resistance to the ordinary cephems as well as fluoroquinolones and the fourth-generation cephems but not to carbenicillin and aztreonam. Rabbit polyclonal antisera and murine monoclonal antibody against the components of the MexA-MexB-OprM system were prepared and used to demonstrate the reduced production of this efflux system in the nfxB mutants. Consistent with this, transcription of the mexA-mexB-oprM operon decreased in an nfxB mutant. This reduction appears to explain the hypersusceptibility of the nfxB mutant to β-lactams, including ordinary cephems.